Notes on European Agromyzidae (Diptera) - 3. - Spencer, Kenneth Angus (Contributions to Entomology = Beiträge zur Entomologie, 1971)
Recent study of the british Agromyzidae (Spencer, in press) has led to the clarification of a number of European species, which are discussed in this paper. The previous paper in this series was published by Spencer (1969b). Four species, previous incorrectly identified, are described below as new; three new synonyms are established; two species, previously synonymised, are now resurrected; and the male genitalia of 17 further species are illustrated. In addition, revised keys are provided for the genere Phytobia Lioy and Amauromyza Hendel.Nomenclatural Actsleonuri Spencer, 1971 (Amauromyza (Amauromyza)), spec. n.mihalyii Spencer, 1971 (Amauromyza (Cephalomyza)), spec. n.strobli (Hendel, 1920) (Amauromyza (Cephalomyza)), comb. n. hitherto Dizygomyza strobliistrobli Hendel, 1920 (Dizygomyza), Lectotype; nom. n. pro obscuripennis Strobl, nec Macquart, 1835laticeps Hendel, 1931 (Dizygomyza (Dendromyza)), syn. n. of Phytobia lunulata (Hendel, 1920)hieracivora Spencer, 1971 (Liriomyza), spec. n.obliqua Hendel, 1931 (Liriomyza), Lectotypeflavoscutellata (Hendel, 1931) (Paraphytomyza), comb. n. hitherto Phytagromyza flavoscutellatabetulae (Kangas, 1935) (Phytobia), comb. n. hitherto Dendromyza (Dizygomyza) betulaelunulata (Hendel, 1924) (Phytobia), comb. n. hitherto Domomyza lunulatamallochi (Hendel, 1924) (Phytobia), comb. n. hitherto Dizygomyza mallochialbiceps Meigen, 1830 (Phytomyza), Lectotypecampanulivora Spencer, 1971 (Phytomyza), spec. n.umbelliferarum Hering, 1935 (Phytomyza), syn. n. of Phytomyza ferulae Hering, 1924